Searching for coherence in language teaching: the issue of teaching competencies - Rico Troncoso, Carlos (Colombian Applied Linguistics Journal, 2005)
This document is an attempt to show some theoretical issues teachers should take into account when adopting the commitment of teaching languages. Many things haven been said about teaching languages, but there has not been any systematic refl ection about teaching a foreign language in our context. Our foreign language history has shown that Colombian teachers implement many things in their classrooms without realizing the impact of those implementations in the theoretical and practical fi eld. Nowadays, some changes have been given to the New ICFES State Examination, and The Ministry of Education (MEN) has proposed in the curricula orientations the language competence education. Due to these new demands, it is necessary to revise the way how a foreign language is taught in our educational context. To this respect, the present paper will mention some of the most important aspects teachers should refl ect upon when dealing with language teaching. The fi rst thing to do is to defi ne the approach or the method to be used (the nature of language and of language learning) second, it is necessary to defi ne the design to be implemented according to the theory proposed. The design will deal with the teaching objectives, the type of syllabus adopted (content choice and organization), the types of learning and teaching activities, the learner and teachers roles, and the role of instructional materials.